Google Data Studio Implementation for Visualizing West Java Province Toddler Stunting Data - Muhammad Rizqi Sholahuddin; Firas Atqiya; Husna Faridah; Nuri Nurianti (The IJICS (International Journal of Informatics and Computer Science), 2022)
One of the world's most critical nutritional issues, stunting is particularly prevalent in impoverished and emerging nations, including Indonesia. West Java is one of the provinces having a relatively high proportion of children with stunted growth. This study intends to conduct data visualization about the number of stunted children under the age of five in each West Java city or district. The data visualization is an interactive dashboard with several interconnected charts that was created using Google Data Studio. This is intended to aid the analysis of the distribution of stunting among children under the age of five in West Java by city and district from 2014 to 2021. Open Data Jabar is the source of the data used to create the visualization of data on toddlers with stunting in West Java. The result of this research is a dashboard that can be facilitate data analysis process. From the dashboard, we can determine that the total number of cases of toddler stunting in West Java reduced between 2014 and 2021. Despite an increase in the number of instances between 2019 and 2020, the number of cases has reduced again in 2021